Body composition and on-ice skate times for national collegiate athletic association Division I collegiate male and female ice hockey athletes - Czeck, M. A.; Roelofs, E. J.; Dietz, C.; Bosch, T. A.; Dengel, D. R. (The Journal of Strength and Conditioning Research, 2022)
This study's purpose was to explore positional differences for an on-ice timed skate test and its relationship to body composition. Male (n = 15) and female (n = 18) collegiate hockey players participated in this study (total n = 33). Each player was categorized by position of forward or defensemen. Dual x-ray absorptiometry assessed total body composition variables of lean, fat, and bone mass as well as regional measures of lean mass, fat mass, and visceral adipose tissue. Total time and section times were determined for the on-ice skating test through a gated automatic timing system at 9, 18, 24, 42, 48, 66, 82, 132, and 148 m. Analysis of variance and Tukey's honest significance difference assessed on-ice skate time differences between positions (p = 0.05). Correlations between body composition variables and skate times were determined for change of direction, skating time, linear skate time, and total skate time. There were no significant differences between positions for skate times (p > 0.05). Body fat percent (p = 0.007; r = 0.55), total fat mass (p = 0.027; r = 0.46), and leg fat mass (p = 0.019; 0.49) were significantly correlated with total skate time in men, whereas only body fat percent was significantly correlated with change of direction (p = 0.022; r = 0.54) and total skate times (p = 0.016; r = 0.56) in women. The total upper-body mass to leg lean mass ratio was significantly correlated with change of direction (p = 0.036; r = 0.50) in women. In conclusion, the results from this study suggest no differences between on-ice skating times between forwards and defensemen. However, body fat percentage was correlated with on-ice skate times in male and female collegiate hockey players.